Revisiting the Dielectric Breakdown in a Polycrystalline Ferroelectric: A Phase‐Field Simulation Study. Issue 1 (3rd November 2022) - Khondabi, Mohammad; Ahmadvand, Hossein; Javanbakht, Mahdi
Abstract: To understand the dielectric breakdown in a polycrystalline ferroelectric, a thorough phase field simulation has been performed by introducing a new degradation function. Time and position evolution of breakdown path, electric field dependence of breakdown time, and the effect of several parameters such as grain orientation, dielectric constant of grain and grain‐boundaries (GBs), thickness of GBs ( d GB ${d}_{\text{GB}}$ ), and grain size ( G a ${G}_{\text{a}}$ ) on the threshold breakdown electric field, E BT ${E}_{\text{BT}}$, are investigated. The results indicate that E BT ${E}_{\text{BT}}$ is improved with decreasing dielectric constant. The dependence of E BT ${E}_{\text{BT}}$ on grain size and GB's thickness obeys a power function G a − n ${G}_{\text{a}}^{-n}$ ( n = 0.42 $n=0.42$ ) and d GB n ${d}_{\text{GB}}^{n}$ ( n = 0.3 $n=0.3$ ), respectively. The results help to engineer the grains and GBs properties and achieve a high breakdown electric field, which is very important in energy‐storage applications. Abstract : By engineering the grains and grain‐boundaries properties (dielectric constant, thickness of grain‐boundaries ( d GB ${d}_{\text{GB}}$ ), and grain size ( G a ${G}_{\text{a}}$ )), a high breakdown electric field, E BT ${E}_{\text{BT}}$, can be achieved for a polycrystalline ferroelectric. E BT ${E}_{\text{BT}}$ enhances with decreasing dielectric constant. A high E BT ${E}_{\text{BT}}$ is achieved by reducing G a ${G}_{\text{a}}$ and increasing d GB ${d}_{\text{GB}}$, through the power functions of ( G a ) − 0.42 ${(G_{\text{a}})}^{-0.42}$ and ( d GB ) 0.3 ${({d}_{\text{GB}})}^{0.3}$ .